Batman a lot of Li'l Gotham - Nguyen, Dustin; Fridolfs, Derek; Temofonte, Saida; Hill John J. (Burbank, CA DC Comics, 2018)
Follows children versions of Batman, Robin, the Joker and other heroes and villains of Gotham City through the holidays.
Keywords: Graphic novels; Superheroes -- Fiction; Supervillains -- Fiction; Holidays -- Fiction